2009
DOI: 10.1161/circinterventions.108.831800.108.831800
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Clinical, Angiographic, and Intravascular Ultrasound Follow-Up of the XIENCE V Everolimus-Eluting Stent in the Treatment of Patients With De Novo Native Coronary Artery Lesions

Abstract: Background-This article reports the 2-year clinical, angiographic, and intravascular ultrasound outcomes of the everolimus-eluting stent (EES) compared with the paclitaxel-eluting stent (PES) in the randomized SPIRIT II trial. Methods and Results-This was a prospective, single-blind clinical trial in which a total of 300 patients with de novo native coronary artery lesions were randomized to either EES or PES in a 3:1 fashion. Clinical follow-up was planned at 2 years in all patients. A subset of 152 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(50 citation statements)
references
References 24 publications
8
39
0
3
Order By: Relevance
“…In particular, the rate of ⌬TLR with the Cypher stent (3.5%) was significantly higher than that with both the Dual-DES and ZES. The observation of a small magnitude "catch up" in antirestenotic efficacy with polymer-based DES has previously been described in earlier reports (4,5,16,17).…”
Section: Angiographic Data At 6 To 8 Months and Composite Angiographisupporting
confidence: 55%
“…In particular, the rate of ⌬TLR with the Cypher stent (3.5%) was significantly higher than that with both the Dual-DES and ZES. The observation of a small magnitude "catch up" in antirestenotic efficacy with polymer-based DES has previously been described in earlier reports (4,5,16,17).…”
Section: Angiographic Data At 6 To 8 Months and Composite Angiographisupporting
confidence: 55%
“…The SPIRIT II trial demonstrated better clinical efficacy and safety of EES compared to the first-generation Taxus Express 2 PES over 4 years of follow-up; longterm follow-up demonstrated "delayed" restenosis with EES, a phenomenon previously observed with other DES [35]. This finding, however, did not appear to have any adverse effect on clinical outcomes.…”
Section: The Xience-v Eesmentioning
confidence: 76%
“…Несмотря на то что стенты с лекарственным пок-рытием заметно снизили частоту рестеноза, длитель-ная персистенция инородного тела в коронарной ар-терии и продолжительное действие лекарственного покрытия препятствуют раннему заживлению сосуда, вызывают локальное воспаление стенки и могут быть причиной позднего рестеноза и тромбоза [30,31]. Так, результаты мультицентрового рандомизированного ис-следования TROfL II trial продемонстрировали лучшие показатели неоинтимального заживления биодегради-руемого стента Absorb, по сравнению с Xience, у паци-ентов с инфарктом миокарда с подъемом сегмента ST через 6 мес.…”
Section: Discussionunclassified